Developing listening techniques to improve oral performance of Intermediate Intensive English II students, in the first semester of 2014 at the Foreign Languages Department in the University of El Salvador - Aguilar Rivera, Yoselyn Guadalupe; Argueta Villegas, Carmen Elena; Recinos Vásquez, Rocío Ivania (2024)
This report intended to draw a broad picture about how the use of listening techniques could influence oral performance. This work documents a research that was carried out by the authors during the first semester of 2014 in the Foreign Languages Department at the University of El Salvador with a sample population of students selected from the different Intermediate II courses of the Teaching Major of the B.A. in English at that time. The purpose of the study was to develop Listening techniques and investigate how these techniques enhanced the oral performance of the students in the class. English learning must be directed to get an outcome, in this case: the usage of English Language to communicate with others in a country where this language is becoming necessary in many fields. English learning as a second language is an integration of the four-macro skills: listening, reading, writing and speaking. Any of these processes can be isolated from the rest, but according to research about the factors influencing listening comprehension in English and possible measures of improvement, Listening is very significant. As a group, we agree that a big part of language learning depends on Listening, since it provides the aural input that serves as the basis for language acquisition and enables learners to interact in spoken communication. Authors consulted express that at the workplace and beyond, a listening period is very important when it is followed by a productive task such as an oral activity since students get new vocabulary, pronunciation, etc. Listening enables oral activities in the classroom; consequently, this experiment aimed to work with Listening techniques and investigate if those techniques improved the oral performance in Intermediate II students.